Extracorporeal Photopheresis in Heart Transplantation: Mechanisms, Clinical Integration, and the Experience of the Azienda Ospedaliera Universitaria Senese - Luca Martini; Francesca Maria Righini; Adelina Selimi; Sonia Bernazzali; Sandro Sponga; Serafina Valente; Massimo Maccherini (Artificial Organs, 2026)
ABSTRACT Backgrounds Extracorporeal photopheresis (ECP) is a promising immunomodulatory strategy for complex rejection in heart transplant (HTx) recipients. By combining leukapheresis, 8‐methoxypsoralen photoactivation, and UVA irradiation, ECP induces leukocyte apoptosis and promotes immune tolerance through dendritic‐cell modulation, regulatory T‐cell expansion, and cytokine reprogramming. Clinical evidence supports its use in steroid‐refractory acute cellular rejection (ACR) and selected antibody‐mediated rejection (AMR). This study reviews the mechanistic rationale and clinical evidence for ECP and reports the real‐world experience of the Azienda Ospedaliera Universitaria Senese (AOU Senese). Methods We retrospectively analyzed a single‐centre cohort of 19 heart transplant recipients treated with extracorporeal photopheresis at AOU Senese between March 2010 and November 2024. Clinical, histological, immunological, echocardiographic, biomarker, immunosuppressive‐treatment, and safety data were extracted at baseline and at dataset‐defined 3‐, 6‐, 12‐, and 24‐month assessments. Analyses were descriptive and used variable‐specific denominators because follow‐up and laboratory data were incomplete at later time points. Results Biopsy data for cellular‐mediated rejection (CMR) were available in 19 patients through 12 months and in 11 patients at 24 months. The proportion with ≥ 1R CMR decreased from 11/19 (57.9%) at baseline to 4/19 (21.1%) at 3 months, 3/19 (15.8%) at 6 months, 2/19 (10.5%) at 12 months, and 0/11 at 24 months. pAMR1 was present in 6/18 (33.3%) patients with available baseline AMR data, absent at 3 months, present in 1/19 (5.3%) at 6 months, and absent among patients with available biopsies at 12 and 24 months. In contrast, Class II DSA positivity did not show a consistent decline (12/19 [63.2%] at baseline and 8/10 [80.0%] at 24 months). Left ventricular systolic function remained broadly preserved among available observations, and corticosteroid dose decreased over time. Seven deaths occurred during the available overall follow‐up, four of which were recorded as reasons for ECP discontinuation. Conclusions In this small, retrospective, uncontrolled, and clinically heterogeneous cohort, ECP use was temporally associated with a lower biopsy‐documented rejection burden and reduced corticosteroid exposure. The study does not establish a causal effect of ECP on rejection, antibody burden, or safety, and the antibody data do not support a uniform reduction in DSA. Prospective multicentre studies with standardized treatment protocols, assay definitions, and complete longitudinal follow‐up are required.